Letters from Readers. (Commentary, 2001)
Presents comments on various articles published in the periodical 'Commentary.' Article about Orthodox Judaism written by David Berger; Actions taken by the United States (U.S.) government against Microsoft Corp.; Comments on the military campaign of the U.S. in Yugoslavia.